At the crack of the bat : baseball poems - Morrison, Lillian; Cieslawski, Steve (New York : Hyperion Books for Children, 1992)
An illustrated collection of poems, by a variety of authors, about the game and personalities of baseball.
"Ages 8-12"--Jacket.
Includes index.
School Library Journal starred
Booklist
Teacher Librarian
6.2
Keywords: Baseball -- Juvenile poetry; Children's poetry, American; Baseball -- Poetry; American poetry -- Collections; Baseball -- Poetry; American poetry -- Collections